COMPARISON (IN-VITRO) OF BEE HONEY WITH ANTIBIOTICS ON MICROORGANISMS ISOLATED FROM INFECTED BURN WOUNDS - Qur at-ul-ain Zahra; Zahid Mahmood Nagra; Samina Qamar (Journal of University Medical & Dental College, 2015)
ABSTRACT OBJECTIVE: To compare the effectiveness of honey with antibiotics on microorganisms isolated from burn wound infections. STUDY DESIGN: experimental study. PLACE AND DURATION: Department of Plastic surgery and Pathology, AHF, PMC, Faisalabad and Department of Biological Sciences, GC University, Faisalabad. METHODOLOGY: The blood/pus specimen collected from ﬁfty burn patients in Dept. of Plastic surgery and Burns,Allied Hospital/Punjab Medical College Faisalabad(from Jan. 2012 to Jul. 2012) were cultured and isolated on different media types. Isolates were then identiﬁed up-to specie level by different biochemical tests. An antibiotic sensitivity pattern against ﬁve most common isolates identiﬁed was measured by using pure honey (Apis mellifera) and antibiotics including Amikacin(AK), Levoﬂoxacin(LEV), Meropenem(MER), Tazobactem(TAZ). RESULTS: Antibiotic sensitivity results showed that Streptococcus spp. gave 26%, 17%, 13%, 4% sensitivity against AK, LEV, MER and TAZ respectively and 40% against honey. S. aureus showed 24%, 18%, 18%, 6% sensitivity against AK, LEV, MER and TAZ respectively, while it was 34% sensitive against honey. Sensitivity showed by E. coli was 28% for AK, 13% LEV, 9% MER, 6% TAZ and 44% for honey. Klebsiella spp. growth was affected 28%, 17%, 10%, 7% against AK, LEV, MER and TAZ respectively, where as 38% against pure undiluted honey. AK (23%), LEV (15%), MER (12%), TAZ (8%) prevented P. aeruginosa growth as compared to (42%) honey